Exploring Self-Directed Learning Strategy to Enhance Students’ Writing Ability: An Autonomous Learning Classroom Practice - Heni Purnama Sari; Dira Permana (Lombok Institute, 2025)
This study seeks to explore the effectiveness of the Self-directed learning strategy to enhance students' writing ability. The study used a pre-experimental study with one group pretest and posttest design, which covered all eight classes of students at MTs. NW Mertak Nao as the population and samples. The instrument used descriptive text writing. The gained scores were analyzed statistically. The statistical analysis showed that the average score of pre-test was 28 and post-test score of the experimental group was 66.82, and the t-test was 4.1560, which was higher than the t-table value of 1.7247 at the significance level of 5% with the number of degrees of freedom was 54. The results of the study found that the Self-directed learning (SDL) strategy effectively enhanced students' descriptive text writing ability. The implementation of the SDL strategy has promoted students’ awareness and self-control to a well-planned learning that successfully encouraged students to participate actively and express their ideas more independently during classroom learning of writing. Independence and responsibility for the learning reflected in the ability of the students to manage time, learning goals, and learning sources has empowered the Self-directed learning strategy to be the successful key in developing student-centered learning. Finally, this finding suggests that teachers should incorporate SDL principles in carrying out writing instruction to have students’ better ability in writing.